The Influence of Work Discipline, Motivation and Work work-life balance on Employee Engagement at PT Bank Syariah Indonesia (BSI) KCP Buah Batu - Sudjati, Levan David; Siddiq, Andhika Mochamad (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This research aims to analyze the influence of work discipline, motivation, and work-life balance on employee engagement at Bank Syariah Indonesia (BSI) KCP Buah Batu 2, using quantitative research methods and descriptive and verification analysis approaches. The primary data was obtained through pre-surveys, questionnaires, document collection, and interviews with Bank Syariah Indonesia (BSI) KCP Buah Batu 2 employees. The research sample was taken using a non-probability sampling method, namely the assessment sample technique, which resulted in 31 people employees as the population and research sample. The results of the regression analysis show that work discipline, motivation, and work-life balance have a significant effect on employee engagement. The coefficient of determination shows a value of 0.699 or 69.9%, which means that overall, the variables of work discipline, motivation and work life balance simultaneously contribute 69.9% to employee engagement. In comparison, 30.1% is influenced by other factors.